THE ROLE OF PRESENTATIONS IN LESSONS OF RUSSIAN FOR NON-LINGUISTIC UNIVERSITIES (Proceedings of International Educators Conference, 2023)
In this article we discussed the roles of presentation and the principles of using technology in Russian language lessons in a non-linguistic universities. That it helps improve the effectiveness of learning, motivate students and improve the quality of educational processes.